Synthesis and Characterization of DNA Minor Groove Binding Alkylating Agents - Iyer, Prema (2012)
Derivatives of methyl 3-(1-methyl-5-(1-methyl-5-(propylcarbamoyl)-1H-pyrrol-3-ylcarbamoyl)-1H-pyrrol-3-ylamino)-3-oxopropane-1-sulfonate (1), a peptide-based DNA minor groove binding methylating agent, were synthesized and characterized. In all cases the N-terminus was appended with a O-methyl sulfonate ester while the C-terminus group was varied with non-polar and polar sidechains. In addition, the number of pyrrole rings was varied from 2 (dipeptide) to 3 (tripeptide). The ability of the different analogues to efficiently generate N3-methyladenine was demonstrated as was their selectivity for minor groove (N3-methyladenine) vs. major groove (N7-methylguanine) methylation. Induced circular dichroism studies were used to measure the DNA equilibrium binding properties of the stable sulfone analogues; the tripeptide binds with affinity that is > 10-fold higher than the dipeptide. The toxicities of the compounds were evaluated in alkA/tag glycosylase mutant E. coli and in human WT glioma cells and in cells over-expressing and under-expressing N-methylpurine-DNA glycosylase, which excises N3-methyladenine from DNA. The results show that equilibrium binding correlates with the levels of N3-methyladenine produced and cellular toxicity. The toxicity of 1 was inversely related to expression of MPG in both the bacterial and mammalian cell lines. The enhanced toxicity parallels the reduced activation of PARP and diminished rate of formation of aldehyde reactive sites observed in the MPG knockdown cells. It is proposed that unrepaired N3-methyladenine is toxic due to its ability to directly block DNA polymerization.